The Use Of Instagram Social Media By The Provincial Government To Increase Accountability And Interaction With Followers - Niluh Ayu Anggaswari; Tine Agustin Wulandari (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2026)
This research examined the use of Instagram social media by the provincial government, specifically the strategy used by the Communication and Information Office of West Java Province through the utilization of Instagram social media as a channel of public communication. Using a descriptive qualitative approach, researchers obtained data through interviews and observations to analyze social media contents. The results of the research indicated that the use of Instagram by the provincial government was able to help improve government accountability and transparency as well as public interaction or involvement consisting of followers and Instagram users in general. Provincial government used various Instagram features to share information and provide direct responses to public questions or statements. This research is expected to be an evaluation for the provincial government to increase engagement with its followers which can be done through content collaboration with influencers and respond to statements or answer public questions more quickly.